Teacher Interaction Analysis by Using Initiation, Response and Feedback (IRF) - Ahadya Rahmania (STKIP AL HIKMAH SURABAYA, 2025)
This study examines how the IRF model and teacher feedback strategies influence student participation in an Indonesian elementary school classroom. By analyzing teacher-student interactions, it aims to highlight the balance between structured instruction and student autonomy in foreign language learning. A summary of a review of foreign language learning for elementary school students regarding recognizing the names of fruits and constructing sentences with the names of these fruits is a good start to learning a foreign language, where students are given a lot of vocabulary as initial capital for them to compose sentences and speak, while the role of the teacher Here, apart from being a material provider, the teacher also becomes a judge who is able to reflect on what students do and provide feedback that builds students to learn English better.